Seasonal Variability of the Daytime and Nighttime Atmospheric Turbulence Experienced by InSight on Mars. Issue 22 (16th November 2021) - Chatain, A.; Spiga, A.; Banfield, D.; Forget, F.; Murdoch, N.
Abstract: The InSight mission, featuring continuous high‐frequency high‐sensitivity pressure measurements, is in ideal position to study the active atmospheric turbulence of Mars. Data acquired during 1.25 Martian year allows us to study the seasonal evolution of turbulence and its diurnal cycle. We investigate vortices (abrupt pressure drops), local turbulence (frequency range 0.01 − 2 Hz) and non‐local turbulence often caused by convection cells and plumes (frequency range 0.002 − 0.01 Hz). Contrary to non‐local turbulence, local turbulence is strongly sensitive at all local times and seasons to the ambient wind. We report many remarkable events with the arrival of northern autumn at the InSight landing site: a spectacular burst of daytime vortices, the appearance of nighttime vortices, and the development of nighttime local turbulence as intense as its daytime counterpart. Nighttime turbulence at this dusty season appears as a result of the combination of a stronger low‐level jet, producing shear‐driven turbulence, and a weaker stability. Plain Language Summary: The weather station on board the InSight lander on Mars includes a very sensitive barometer to measure atmospheric pressure all the time. We use pressure records by InSight during more than a Martian year to study how the fast (from seconds to minutes) changes in the atmosphere (named turbulence) varies with seasons on Mars. Because of the heating of Mars surface by sunlight, turbulence during the day is strong and takes the form of convection plumes and whirlwinds that are detected by InSight. At night, turbulence is usually not expected because the colder surface prevents convection to occur. We discovered that turbulence at InSight landing site was unusual in autumn/winter: daytime whirlwinds are much more numerous, whirlwinds form even during the night, and there is nearly as much turbulence during the night than during the day. We explain the increase of nocturnal turbulence at this dusty season on Mars by warmer and windier nights. Key Points: InSight's pressure sensor unveils seasonal variability of daytime and nighttime atmospheric turbulence on Mars Local turbulence ( > 0.01 Hz) is sensitive to wind at all local times and seasons contrary to non‐local turbulence ( < 0.01 Hz, i.e., plumes/cells) Northern autumn/winter hosts a remarkable burst of daytime vortices, and nighttime turbulence (including vortices) triggered by strong wind